Pengaruh Persepsi Manfaat, Persepsi Kemudahan Terhadap Minat Menggunakan Aplikasi Fintech dengan Kepercayaan Sebagai Variabel Intervening pada Generasi Z Kota Medan - Nurhayati; Ade Gunawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of perceived ease and perceived usefulness on interest in using fintech applications through trust. This research adopts a quantitative associative methodology, where every individual from generation Z who lives in the city of Medan becomes the population and sample. To determine the sample size, the Lemeshow method was used, which determined a minimum of 384 respondents to participate to fill out a questionnaire with a Likert scale. The collected data was then analyzed using the PLS-SEM approach with the SmartPLS tool. Research findings reveal that perceived convenience has a significant influence on interest in using fintech applications. Perception of ease has a significant effect on confidence in using fintech applications. Perceived benefits have a significant effect on interest in using fintech applications. Perceived benefits have a significant effect on confidence in using fintech applications. Trust has a significant effect on interest in using fintech applications. Perception of ease has a significant effect on interest in using fintech applications through trust. Perceived benefits have a significant influence on interest in using fintech applications through trust in generation Z in the city of Medan.